The effect of traditional Thai massage vs routine physical therapy on gait pattern in spastic cerebral palsy: A cross-over randomized controlled trial - Peerapat Lertwiram; Chanika Angsanuntsukh; Krongkaew Supapitanon; Tanyaporn Patathong; Apiphan Iamchaimongkol; Suchanont Baosuwan; Ponsaphat Ongtanasin; Phimpisut Srinorasit; Patarawan Woratanarat (PLoS ONE, 2025)
Background Various types of massage, including the traditional Thai, have not yet provided conclusive evidence to reduce the spasticity and improve walking ability for cerebral palsy (CP). Objectives To assess the effect of traditional Thai massage (TM) vs. a standard physical therapy (PT) on gait pattern in spastic CP. Methods A cross-over single blinded randomized controlled trial was conducted between October 2022 and October 2023 (Thai Clinical Trials Registry: TCTR20220530007). Individuals with aged 5 years or older, and diagnosed as spastic CP, Gross Motor Function Classification System (GMFCS) I-III were recruited. Participants were randomly assigned into group A (TM followed by PT), and group B (PT followed by TM). Each treatment lasted for 6 weeks (Phase I-II), with a 6-week washout period. Lower extremity range of motion, muscle tone, electromyography, gait profile score (GPS), oxygen consumption was blindly assessed and intention-to-treat analyzed. Results From 32 eligible patients (16 cases per group), average age was 16.1 ± 9.8 years (group A), and 13.6 ± 5.8 years (group B). Group B demonstrated higher left ankle dorsiflexion than group A (1.7 ± 13.0 degrees vs 12.1 ± 6.9 degrees, P-value = 0.011). GPS slightly improved in Phase I, and contradictory enhanced in TM while deteriorated in PT in Phase II without significant differences between groups. After adjusted for ankle dorsiflexion, TM significantly provided less overall GPS (-1.6 (95% confidence interval (CI) -2.6, -0.6), P-value = 0.001), and higher peak activity of right rectus femoris (0.132 mV (95%CI 0.001, 0.262), P-value = 0.030) compared to PT. Other outcomes did not differ significantly between two treatments, and no complication was detected. Conclusions TM has a positive effect on gait performance, as indicated by GPS and increased activity in the right rectus femoris muscle when compared to PT. A large-scale non-inferiority trial is required to affirm the impact of TM.